Adopting a Blended Learning Approach: Challenges Encountered and Lessons Learned in an Action Research Study - Kenney, Jane; Newcombe, Ellen (Online Learning, 2011)
Adopting a new teaching approach is often a daunting task especially if one is an early adopter in a limited-resource environment. This article describes the challenges encountered and the strategies used in pilot testing a blended instructional method in a large size class within the college of education at a medium-sized university. The main reasons for using the hybrid method were to improve student participation, preparation, and understanding as well as to encourage a more active rather than passive approach to learning which can be particularly difficult in large-sized, undergraduate courses. An action research study was used to document the adoption process and to measure the impact of the blended approach. The results of the action research study and the issues and barriers encountered when implementing a new instructional strategy are discussed as well as ideas for motivating and helping faculty when there is limited funding, training, and support available.